Constructing a Periphery: Descriptions of Hungarian, Transylvanian, and Croatian Towns in Theater Periodicals in the Holy Roman Empire, 1760–1800 - Muresan, Raluca (Historical Studies on Central Europe, 2022)
Based on the analysis of articles published in theater periodicals in the Holy Roman Empire, this study explores the enlightened cultural and symbolic geographies as reflected in the late eighteenth-century German theatrical press. Larry Wolff has shown that western travelers tend to locate the borders of civilized Europe in Habsburg lands situated east of Vienna, namely in Galicia and Hungary. If theatrical periodicals and travel memoirs by western travelers share a common interest in the frontiers of civilized Europe, the specific geography of civilization entails several contradictions in the two medias. Larry Wolff has shown that western travelers tend to locate the borders of civilized Europe in Habsburg lands situated east of Vienna, namely in Galicia and Hungary. By contrast, in theatrical journals based in the Holy Roman Empire, the borders of civilization seem to be concentrated south-eastwards, along the Ottoman frontier, namely in Hungary and in the countries of St. Stephen’s Crown. The article seeks to elucidate variations by pointing to geographical and political factors, as well as to differences between these two literary genres. Unlike travel journals, theater periodicals in the Holy Roman Empire had to give a general overview of contemporary theater life, by pointing to the mobilities of itinerant theatrical, especially German, companies, and by documenting their repertoire. This article reveals how the specific construction of an imagined European periphery reflected by the periodicals is determined both by their networks of contributors and by the taste for exotic, namely Turkish subjects, in eighteenth-century dramas and operas. Hence, such philosophic geographies are shaped both by the origin, the language, the genre and by the major themes of such periodicals.